Leo Divendal : théâtres d’ombres - Campeau, Sylvain (CV Photo)

(untitled) (Les Productions Ciel variable, 1999)
Summary As a photographer, Leo Divendal is known for his recapturing of archival images, without added legend. In the series presented here, he accumulates portraits, park scenes, children's games - all engulfed in a halo of opaline light. To these images, he adds others, taken in Terezin, Czech Republic, of buildings that today are the remains of a concentration camp to which four of his great-aunts were probably sent. In this succession of contrasting images, each image is imbued with a hidden meaning. Divendal, the delver into archives, provides here an experience that is almost existential. As a compiler of archives, he measures himself against a buried memory that has not yet touched his own.